2022
DOI: 10.24925/turjaf.v10i2.374-380.4648
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Rice Farmers to Climate Change in Kwara State, Nigeria

Abstract: Climate unpredictability and weather extremes are being projected as capable of presenting additional challenges for farmers currently engaged in the low-technology based food production systems in sub-Saharan countries like Nigeria. This study assessed rice farming households’ vulnerability to climate change in Kwara State, Nigeria. Primary data, collected from 150 respondents using simple random sampling procedure were analysed employing descriptive statistic was use to describe the coping strategies adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Indicator normalization using a functional relationship was adapted from the Human Development Index (HDI), which has been employed by both United Nations Development Programme (UNDP) and the Organization for Economic Co-operation and Development (OECD). This methodology entails ensuring that all indicator values can be effectively compared and harmonized, resulting in their standardization within a uniform range, typically spanning from 0 to 1 [15]. Vulnerability increases with exposure and susceptibility but reduces with adaptive capacities.…”
Section: Vulnerability Assessmentmentioning
confidence: 99%
“…Indicator normalization using a functional relationship was adapted from the Human Development Index (HDI), which has been employed by both United Nations Development Programme (UNDP) and the Organization for Economic Co-operation and Development (OECD). This methodology entails ensuring that all indicator values can be effectively compared and harmonized, resulting in their standardization within a uniform range, typically spanning from 0 to 1 [15]. Vulnerability increases with exposure and susceptibility but reduces with adaptive capacities.…”
Section: Vulnerability Assessmentmentioning
confidence: 99%
“…Nosiru et al (2014) found farmers' age to have a negative influence on total productivity. Furthermore, climate change influences rice yield (Sarker et al, 2013;Akanbi et al, 2022;Heriansyah et al 2022). The extent of per capita land area of rice harvested rather than yield per hectare is the key determinant of rice production in Southeast Asia (Dawe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was done in southwestern Nigeria where farm size cultivated, frequency of extension contacts, and yield ratings of improved varieties are the key factors for adoption (Saka and Lawal, 2009). Climate change affects rice farmers and thus, it is advocated that capacity building at the farm level which is key to improving crop, soil, and water management be provided with an expansion of irrigation and effective extension service delivery (Akanbi et al, 2022). Pest infestation and difficulties of finance are the major constraints for rice farmers in Ekiti State, Nigeria (Osanyinlusi and Adenegan, 2016).…”
Section: Introductionmentioning
confidence: 99%